ID 337 – Response to clonazepam in typical absence status epilepticus. Issue 3 (March 2016) - Abdellaoui, W.; Bahbouh, S.; Benalia, R.; Belabed, M.R.; Attal, E.; Ait-Kaci-Ahmed, M.
Abstract : Objective: Absence status epilepticus ASE is a type of non convulsive status epilepticus in which continuous or recurrent generalised epileptiform discharges are associated with a varying grade of consciousness.We describe the case of an elderly man who presented with typical ASE resolved after intravenous clonazepam. Methods: Clinical case report. Results: A 62-year old man had a history of idiopathic generalised epilepsy with tonic-clonic seizures.Treated since the age of 30 years with phenobarbital PB 100 mg/day.He was disoriented to time and place and a slowness in mental activity over 24 h after food poisoning. Laboratory tests and a CT scan of the brain were normal.brain MRI did not show any structural lesions.EEG showed recurrent generalsed paroxysms of 3 Hz spike-wave.Normal background activity.Normalisation of mental status and EEG pattern after 1mg intravenous clonazepam (Benzodiazepine). Phenobarbital PB was substituted by valproic acid 1500 mg/day. Conclusion: Typical ASE diagnosis must be based on EEG pattern and clinical history. Efficacy of intravenous clonazepam in treatment of typical ASE.